1-Bit dual-polarized ultrathin lens antennas based on Huygens’ metasurface - Xue, Chunhua; He, Qingqi; Li, Teng; Gao, Xi (Frontiers in Materials, 2022)
In this paper 1-bit dual-polarized ultra-thin lens antennas are presented based on Huygens’ principle. The unit cell provides two-state transmission phase compensation for dual-polarized waves. By tuning state 0 away from resonance and state 1 near Huygens’ resonance, the 180° transmission phase difference between the two states is achieved. In the frequency range of 27.5~28.5GHz, the transmission phase difference between the two states of the unit cell is 180°±20°, and the transmission amplitude is greater than -2dB. Using the proposed unit cell, three ultrathin 1-bit Huygens’ metasurface antennas comprising 33 × 33 unit cells with single beams pointing separately at 0°, 15°, and 30° are designed, fabricated and measured. Simulated and measured results show that the proposed 1-bit transmitarray antenna can achieve single-beam patterns, which is useful for the development of reconfigurable transmission and digital metasurface antennas in the future.